To history of forming and development of science on the stations and knots in the Russian Empire - O. H. Strelko (History of science and technology, 2013)
In the article history of forming and development of science about the stations and knots in the Russian Empire has been highlighted . It is shown that Ukrainian/Russian scientists and engineers were the first to work out the classification of railheads, principles of their planning, bases of specialization of the ground development, methodology of calculation of the station devices, including sorting hills.